2020
DOI: 10.1039/d0cy00817f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of small promoter amounts on coke structure in dry reforming of methane over Ni/ZrO2

Abstract: Choosing the correct alkali metal as a promoter not only reduces coke formation in dry reforming of methane but also removes coke via gasification.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…On the other hand, several promoters such as noble metals, alkali, alkaline earth, and rare metals have been used to promote the performance regarding the activity and stability of Ni nanocatalysts. [26][27][28][29][30] In recent years, automated devices and high-throughput experiments have been developed for the synthesis and evaluation of nanomaterials. [31][32][33][34][35] In addition, computational simulation using density functional theory (DFT) of surface reactions has become an effective tool for the design and performance elucidation of new catalysts by using energies calculated from the activation and reaction of active nanomaterial surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several promoters such as noble metals, alkali, alkaline earth, and rare metals have been used to promote the performance regarding the activity and stability of Ni nanocatalysts. [26][27][28][29][30] In recent years, automated devices and high-throughput experiments have been developed for the synthesis and evaluation of nanomaterials. [31][32][33][34][35] In addition, computational simulation using density functional theory (DFT) of surface reactions has become an effective tool for the design and performance elucidation of new catalysts by using energies calculated from the activation and reaction of active nanomaterial surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several promoters such as noble metals, alkali, alkaline earth, and rare metals have been used to promote the performance regarding the activity and stability of Ni nanocatalysts. 26–30…”
Section: Introductionmentioning
confidence: 99%
“…13–15 Therefore, it remains a great challenge to synthesize the DMR catalyst with excellent activity and stability. To enhance the catalytic performance of the DMR catalyst, numerous studies have been carried out on the effects of the support 16,17 and promoter 18,19 of CH 4 –CO 2 reforming catalysts.CH 4 → C + 2H 2 2CO → CO 2 + C…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the deposition of carbon, the catalysts can be altered by the addition of promoters, being alkaline and alkaline earth metals. 34 Cao et al ; examined the effect of cerium promoter on the activity of cobalt over gamma-alumina applied in dry reforming of methane. 35 They found that the dispersion of the active metal over the support and its reducibility was markedly improved.…”
Section: Introductionmentioning
confidence: 99%